Human umbilical cord mesenchymal stem cells suppress lung cancer via TLR4/NF-κB signalling pathway. Issue 1 (1st January 2020) - Li, Lu; Pan, Jiongwei; Cai, Xiaoping; Gong, Enhui; Xu, Cunlai; Zheng, Hao; Cao, Zhuo; Yin, Zhangyong
Abstract: The present study investigated the inhibitory effect of human umbilical cord mesenchymal stem cells (hucMSCs) on the growth of lung cancer in mice and its relationship with the TLR4/NF-κB signalling pathway. A mouse model of Lewis lung cancer was constructed by inoculating mice with Lewis lung cancer cell suspension under the axilla. Twenty mice were randomly and evenly divided into experimental group and control group. The experimental group received a caudal vein injection of 1 × 10 6 hucMSCs each week for two consecutive weeks, and the control group, an equal amount of saline at the same time. Two weeks after treatment with hucMSCs, the mice were sacrificed and the tumour volume and tumour weight were recorded. Enzyme-linked immunosorbent assay was used to determine the IL-1, IL-6 and TNF-α contents in lung cancer tissues; real-time polymerase chain reaction, to measure the level of mRNA; and Western blotting, to determine the protein expression. The results showed that injection of hucMSCs inhibited the growth of Lewis lung cancer tissues, reduced Lewis lung cancer tissue weight, enhanced thymus index, and suppressed inflammatory responses. hucMSCs inhibited the expression of inflammatory factors IL-1, IL-6 and TNF-α by activating TLR4/NF-κB signalling pathway, and facilitated the expression of Bax. Moreover, huMSCs induced the expression of apoptogenic factor Bax by activating TLR4/NF-κB signalling pathway, and inhibited the expression of antiapoptotic factor bcl-2. The present study demonstrates that hucMSCs reduce inflammatory responses by mediating TLR4/NF-κB signalling pathway, promote apoptosis of tumour cells, and inhibit tumour proliferation in mice with Lewis lung cancer.